Program renewal: Re-evaluating teaching pedagogy in auditing - Sexton, N. D.; Rudman, R. (South African Journal of Higher Education, 2021)
Accounting graduates are entering an uncertain, rapidly changing world that calls for the enhancement of the pedagogy to prepare them for their future world of work. Technical competence needs to be scaffolded with enabling (professional) competencies more than ever before and deep learning is required for students to apply principles in any context. With this in mind, the lecturers at a South African university disrupted (i.e., significantly changed) how a keystone topic in third-year auditing is taught; specifically by creating blended learning interventions for reflection, collaboration, communication, and ethical considerations not previously used in auditing education. This research presents the student perceptions about the appropriateness of these interventions.